Balancing Development and Sustainability in Tourism Destinations : Proceedings of the Tourism Outlook Conference 2015 / [Edited by] Akhmad Saufi,...[et al.] - Lew, Alan Aedited
Includes bibliographical references (pages 409-410) and index.